Analisis perbandingan tone dalam novel "bumi manusia" karya pramoedya ananta toer dan "the catcher in the rye" karya j. D. Salinger - kamilah, Rohmatul (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze and compare the tones used by Pramoedya Ananta Toer in human Earth novels and J.D. Salinger in The Catcher in the Rye with the stylistic approach of Gorys Keraf and the theory of literary acceptance. Research uses descriptive qualitative designs as well as comparative literary perspectives. Data in the form of text pieces representing tones are analyzed through in-depth reading and understanding stages, marking, classification, and interpretation of the reader's reception. Research results show that the human earth is dominated by the melancholy-critical tone, while The Catcher in the Rye is dominated by the melancholy-sarcastic tone. Both use a melancholy tone to strengthen the theme of the old days and their continued impact. The results of this study not only comprehensively answer the problem formulation but also enrich the discourse on cross-cultural comparative literature, particularly in the digital era, where individual reading interest remains low in Indonesia. For future research, it is recommended to expand the scope of analysis to other novels with similar themes from different cultural contexts or backgrounds.